ANALYSIS OF ROAD GEOMETRY CALCULATION BASED ON ROAD GEOMETRIC DESIGN GUIDELINES: CASE STUDY OF PARAGLIDING TOURISM ROAD, MAJALENGKA - Agung Nur Hidayat; Ade Jaya Saputra; Adinda Fajarika (Fakultas Teknik Sipil dan Perencanaan, 2024)
Geometric planning is part of road planning that focuses on physical form so that the main functions of the planned road can be fulfilled. The main function of the road is to provide optimal service in traffic flow and access from one place to another. Geometric planning also has an important role for the economy of a region, with road geometric planning making it easier for people to reach areas that are difficult to reach but has the potential to improve the regional or national economy. A country that desperately needs to upgrade its infrastructure to improve the living standards and well-being of its people. To achieve this goal, the country needs various supporting factors, including infrastructure. The latitude of the research location is between -6,846,332,965 to -6.850200754, while the longitude is between 108203130505 up to 108.199008503, with a horizontal alignment of 112 m and a vertical alignment gradient of 3.43 %.